Diagnosis and grading of carpal tunnel syndrome with quantitative ultrasound: Is it possible? - YAĞCI, İLKER (ELSEVIER SCI LTD, 2020)
The recent diagnostic tools for carpal tunnel syndrome (CTS) include nerve conduction studies (NCS) and ultrasound (US). Quantitative US (QUS) can be used for demonstrating muscle changes according to denervation. The aim of this study was to evaluate if QUS can diagnose and grade the severity of CTS. In this single blinded cross-sectional study, female patients diagnosed with CTS and age-matched healthy female subjects were included in the study. Median and ulnar nerve conduction studies (NCS) were performed for CTS diagnosis. Median and ulnar nerve cross-sectional area (CSA) was measured, and the abductor pollicis brevis (APB) and abductor digiti minimi (ADM) muscles were longitudinally and transversally visualised. Axial images were analysed for echo intensity (El) via computer-assisted, grayscale analysis. Intra-rater and inter-rater reliability analysis was performed. The Boston questionnaire was used for the evaluation of symptom severity and functional status. Forty-two patients (42 hands) and 32 controls were included. In the CTS group, 17 patients had mild, 13 patients had moderate, and 12 patients had severe CTS. CSA of the median nerve and APB echo intensity was significantly higher in patients with CTS. However, according to the CTS grade, no significant difference was detected for APB El. The intraclass correlation coefficient (ICC) was calculated as 0.928 for intra-rater reliability and 0.768 for inter-rater reliability. QUS evaluation is helpful for the diagnosis of CTS, but not for grading. Further studies are needed with a larger population including both genders. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Carpal tunnel syndrome; Electrodiagnosis; Echo intensity; Quantitative ultrasound; MUSCLE ULTRASONOGRAPHY